CO tolerance of a Pt3Sn(111) catalyst in ethanol decomposition1. Issue 6 (27th June 2015) - Lu, Xiaoqing; Deng, Zhigang; Wei, Shuxian; Zhu, Qing; Wang, Weili; Guo, Wenyue; Wu, Chi-Man Lawrence
<x xml:space="preserve">Abstract</x> The alloying element Sn plays bifunctional and ligand effect roles to strengthen the O-end species adsorptions, adjust the electronic structures, weaken the Pt–CO bonds, and thus enhance the CO tolerance of Pt3Sn(111).